Clinical efficacy of Bufei Yishen and Qutan Tongluo Cream on the treatment of patients with stable chronic obstructive pulmonary disease - Zhang, Huicong; Zhou, Youxia; Song, Gang (Frontiers in Medicine, 2025)
BackgroundTraditional Chinese medicine has been used for the treatment of chronic obstructive pulmonary disease (COPD). However, the effect of Bufei Yishen and Qutan Tongluo Cream (BYQTC) on the amelioration clinical symptoms of COPD remains unclear.MethodsThe enrolled COPD patients were randomly divided into control and observation groups. The efficacy of BYQTC was assessed by the reduction rate of syndrome scores. The improvement effect of BYQTC in COPD patients was evaluated using forced expiratory volume in 1 s, 6-minute walk test, modified British Medical Research Council and COPD Assessment Test. The level of serum interleukin 8 (IL-8) and matrix metalloproteinase 9 (MMP-9) was evaluated by enzyme-linked immunosorbent assay.ResultsThe observation group had a higher clinical control and effectual rate than the control group. After treatment, the improvement of pulmonary function and movement endurance in the observation group was stronger than that in the control group. Meanwhile, the clinical symptoms of COPD were alleviated more in the observation group. Additionally, the decrease in serum IL-8 and MMP-9 levels in the observation group was higher than that in the control group. Finally, the acute exacerbation and rehospitalization of the COPD patient in the observation group was less than that in the control group.ConclusionBYQTC significantly enhances the efficacy of conventional therapy in stable COPD patients, resulting in improvements in clinical symptoms, lung function, and overall quality of life. Notable enhancements were observed in FEV1%, 6MWT distance, and reductions in mMRC and CAT scores. Additionally, BYQTC treatment led to substantial decreases in IL-8 and MMP-9 levels, and reduced the incidence of acute exacerbations and rehospitalizations, demonstrating its superior therapeutic benefit compared to standard treatment.